RISIKO PENCEMARAN BAKTERIOLOGIS SUMUR GALI DAN PAMSIMAS DI WILAYAH KERJA PUSKESMAS KUSUMA BANGSA KOTA PEKALONGAN (BACTERIOLOGICAL POLLUTION RISKS OF THE DUG-WELL AND PAMSIMAS AT PUBLIC HEALTH SERVICEKUSUMA BANGSA, PEKALONGAN) - Sri Mawar; Rosmiati Saleh; Supriyo Supriyo (Prodi Keperawatan Purwokerto, 2013)
Background: The consumption of the dug-well for drinking water, mostly done by most people, not only symbolizing relatively the low level of social-welfare but also indicating that they still can’t afford to access or use pamsimas (social-based-drinking-water provider).Method: Results of a preliminary study of laboratory test to the samples of water, taken from the three dug-wells and the pamsimas showed that all the samples taken from the dug-wells are unqualified, while one of the three samples taken from the water-pipe connection of pamsimas is unqualified. Crowded housing conditions of settlement with each of the homes that have sources of pollution. This study is an observational study with cross sectional method. Data analysis will be performed univariate statistical analysis, bivariate analysis with the chi square test, and multivariate analysis with logistic regression.Results: Results of the research showed there are four variables that have a relationship with the bacteriological quality of water that is the condition of the walls dug wells, wells with absorption distance, distance livestock barns and wells with spacing wells with waste disposal. For wells with variable diffusion distance, a distance well with livestock barns and wells within the landfill has a protective factor against the bacteriological quality of water dug so there are some wells that have close proximity to the sources of pollutants have bacteriological quality status and well qualified with a distance away with blackened sources have bacteriological quality status that do not meet requirements. That is because at the time of observation and measurement, researchers do not pay attention to other sources of pollution of the environment adjacent to the dug well studiedConduction: For other researchers who will conduct research on the status of the bacteriological quality of water wells dug, are expected to pay attention to the sources of contamination adjacent to the dug well studied.